ECONOMICS ON REARING INDIGENOUS AND BROILER BIRDS IN INTENSIVE SYSTEM OF MANAGEMENT - Mustafizur Rahman; Ramijur Rahman; Subham Kumar Pandey; Zahidur Hasan Alom (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was carried out in the month of September, 2022 to know the economics on rearing of indigenous (local) comparative broiler birds at the Poultry Unit of SCS college of Agriculture, Rangamati, Assam Agricultural University, Dhubri, Assam. For the study, day old chicks of indigenous and broiler, 100 numbers each were introduced in deep litter system of management. Broilers were marketed at the completion of 6 th week, while the indigenous birds were kept up to 8 th week and then marketed. Mean body weight was found to be 2082.67±14.85 g and 658.29±3.49 g in the case of broilers and indigenous birds at 6 th week and 8 th week respectively. The feed conversion ratio (FCR) was recorded as 1.64 and 2.29 for broiler and indigenous birds, respectively. The cost of production per kg bird is Rs.114.70 and Rs. 227.90 for broiler and indigenous birds respectively. The net profit calculated in production of broilers and indigenous was Rs. 5100.00 and Rs. 7450.00 respectively. Benefit cost ratio (BCR) in broiler and indigenous bird was found to be 1.22.1.00 and 1.53:1.00, respectively.